China’s Investment in the East Coast Railway Line (ECRL) Project in Malaysia as a Strategisation of Space - Saraswati, Dini Putri; Nasrum, Arnaldi (FISIP UPNVJ, 2023)
The rise of China’s power has led the country to fulfil more energy supply to sustain its industrial development. However, the Straits of Malacca challenges disturbed China’s interest to transport oil from the Middle East. Hence, China chooses the BRI project to maintain the problem. This paper will try to examine China’s strategy of constructing an ECRL project in Malaysia as one of the BRI projects to be an alternative to fulfil its energy supply. This qualitative research will employ the concept of power and connectivity. The use of the ECRL Project to Strategise Chinese Interest in energy supply will also be explained to answer the research questions.